Wireless Multi-nodes Environment Monitoring System Based on Microcontroller, GPS/GPRS/GSM and Google Map - Viet, Nguyen Canh; Tuan, La Minh; Viet, Vu Quoc (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abstract: In this report, a wireless multi-nodes integrated system based on microcontroller, GPS/GPRS/GSM and Google map for wide-area environmental monitoring has been studied and implemented. The system enables us to view the historical and current data recorded of nodes on Google map through a designed website. The environmental data and location of each node are collected and sent to a web server through GPRS service. The web application is developed using PHP, JavaScript and MySQL in combination with embedded Google map service to retrieve and display the data in details. Besides, several commands are also designed for managing the nodes via SMS messages. Keywords: Environmental Monitoring System, GPS/GPRS/GSM, IoT.